A Step to be a Green School: As Addition Green Space to Support Sustainable Living [A Step to be a Green School: Sebagai Penambahan Ruang Terbuka Hijau guna Mendukung Hidup Berkelanjutan] (Jurnal Pengabdian Isola, 2024)
A step to be  a green school ini bertujuan untuk membentuk kesadaran diri peserta didik dalam menjaga pelestarian lingkungan melalui kegiatan sosialisasi serta pembuatan taman sekolah. Tahapan kegiatan ini meliputi: 1) persiapan; 2) penyuluhan proyek dan pembuatan taman sekolah; dan 3) tindak lanjut. Subjek kegiatan ini sebanyak 27 peserta didik kelas VII di salah satu sekolah di Jawa Barat. Untuk mengetahui dampak kegiatan, digunakan angket sebelum dan sesudah kegiatan terkait kesadaran peserta didik terhadap lingkungan. Hasil pengolahan dan analisis data menunjukkan bahwa peserta didik merasakan keuntungan dengan adanya taman sekolah dan terjadi peningkatan rata-rata skor kesadaran lingkungan sebelum dan sesudah kegiatan di semua aspek yang dievaluasi.This study aims to build students' self-awareness in preserving the environment through socialization activities and creating school gardens. This activity was conducted in several stages: 1) preparation; 2) project counseling and making school gardens; and 3) follow-up. After the implementation activities, the questionnaire results were analyzed using descriptive statistics. The research subjects were 27 students from one of the schools in West Java. Data analysis revealed that students recognized a change in their environmental awareness before and after the implementation of the school garden. Students considered the benefits of the school garden, resulting in an increase in the average environmental awareness score across all evaluated aspects before and after the activity.